Spatial Distribution of Plasmodium falciparum and Plasmodium vivax in Northern Ethiopia by Microscopic, Rapid Diagnostic Test, Laboratory Antibody, and Antigen Data. (10th October 2021) - Leonard, Colleen M; Assefa, Ashenafi; Sime, Heven; Mohammed, Hussein; Kebede, Amha; Solomon, Hiwot; Drakeley, Chris; Murphy, Matt; Hwang, Jimee; Rogier, Eric
Abstract: Background: Determining malaria transmission within regions of low, heterogenous prevalence is difficult. A variety of malaria tests exist and range from identification of diagnostic infection to testing for prior exposure. This study describes the concordance of multiple malaria tests using data from a 2015 household survey conducted in Ethiopia. Methods: Blood samples (n=2279) from 3 regions in northern Ethiopia were assessed for Plasmodium falciparum and Plasmodium vivax by means of microscopy, rapid diagnostic test, multiplex antigen assay, and multiplex assay for immunoglobulin G (IgG) antibodies. Geospatial analysis was conducted with spatial scan statistics and kernel density estimation to identify malaria hot spots by different test results. Results: The prevalence of malaria infection was low (1.4% by rapid diagnostic test, 1.0% by microscopy, and 1.8% by laboratory antigen assay). For P. falciparum, overlapping spatial clusters for all tests and an additional 5 unique IgG clusters were identified. For P. vivax, clusters identified with bead antigen assay, microscopy, and IgG partially overlapped. Conclusions: Assessing the spatial distribution of malaria exposure using multiple metrics can improve the understanding of malaria transmission dynamics in a region. The relative abundance of antibody clusters indicates that in areas of low transmission, IgG antibodies are a more useful marker to assess malaria exposure. Abstract : Assessing the spatial distribution of malaria exposure using multiple metrics can improve understanding of malaria transmission dynamics in a region. In low-transmission areas, antibody data provide a useful marker to assess malaria exposure and indicate areas for further study.